PENGEMBANGAN MODEL QUANTUM READING YANG BERORIENTASI SELF REGULATED LEARNING (SRL) DALAM PEMBELAJARAN MEMBACA PEMAHAMAN - Nina Retnaningtyas; Vismaia Damaianti; Syihabuddin Syihabuddin (STKIP Siliwangi, 2022)
Reading is a skill that must be possessed by students. Ideally, every student has adequate reading skills according to their level of education. This is because in daily activities at school, all learning activities cannot be separated from reading skills. However, in reality, many students do not have adequate reading skills, both reading comprehension and creative reading. The learning model cannot be separated from the success of a lesson. The aims of this study were (1) to determine the condition of the reading comprehension learning model in SMP Negeri 1 Purbalingga; (2) to know how the profile of the Quantum Reading model is; (3) to determine the effectiveness of the Quantum Reading Oriented Self-Regulated Learning (SRL) learning model in learning reading comprehension. The research method used is the development method with the stages of preliminary studies, literature studies, and field surveys; limited model development phase and expanded trial; the model validation stage is in the form of an experiment. The research results obtained are (1) the conditions for using learning models in reading comprehension at SMP Negeri 1 Purbalingga before the research was carried out using quantum reading, only using the direct method and assignments; (2) Quantum Reading learning is considered effective in improving students' reading comprehension skills at SMP Negeri 1 Purbalingga (3) with Self-Regulated Learning (SRL) orientation, students understand reading better, as a basis for carrying out the teaching and learning process in any subject.